2000
DOI: 10.1200/jco.2000.18.6.1324
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Disease-Free Survivors in Metastatic Undifferentiated Carcinoma of Nasopharyngeal Type

Abstract: PURPOSE: To review incidence and analyze profile of long-term complete responders among patients with undifferentiated carcinoma of nasopharyngeal type (UCNT) treated at a single institution. PATIENTS AND METHODS: We present a cohort of 20 long-term unmaintained complete responders to chemotherapy for metastatic UCNT treated at the Institut Gustave Roussy between April 1978 and November 1996. A patient was considered a long-term survivor if he or she was disease-free for more than 36 months without treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
108
2
6

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(120 citation statements)
references
References 32 publications
4
108
2
6
Order By: Relevance
“…In fact, one patient survived 8 years 7 months while another three lived beyond 4 years after diagnosis of metastatic disease. A number of studies have reported similar findings, with several long-term survivors with the use of chemotherapy in metastatic NPC (Chan et al, 1997;Fandi et al, 2000). Based on the results of our studies, it is possible for single-arm studies or randomised studies that are inadequately powered or stratified to report spuriously improved survival outcome with a new therapeutic intervention because of biased patient selection alone.…”
Section: Discussionsupporting
confidence: 71%
“…In fact, one patient survived 8 years 7 months while another three lived beyond 4 years after diagnosis of metastatic disease. A number of studies have reported similar findings, with several long-term survivors with the use of chemotherapy in metastatic NPC (Chan et al, 1997;Fandi et al, 2000). Based on the results of our studies, it is possible for single-arm studies or randomised studies that are inadequately powered or stratified to report spuriously improved survival outcome with a new therapeutic intervention because of biased patient selection alone.…”
Section: Discussionsupporting
confidence: 71%
“…In our study metastatic disease had significantly poor prognostic outcome (p \ 0.001). This finding was similar to other studies [9][10][11][12]. Significant survival advantage was seen in patients receiving higher total radiotherapy dose ([66 Gy), which was similar to other studies [13,14].…”
Section: Discussionsupporting
confidence: 92%
“…Although the prognosis of metastatic NPC is still quite poor, it has been well accepted that the survival can be highly variable and long-term survival is possible in some patients (Teo et al, 1996;Fandi et al, 2000;Khanfir et al, 2006). But most of the reports included patients who developed metastasis (es) after primary treatment, few explored the prognosis of newly diagnosed metastatic NPC specially.…”
Section: Discussionmentioning
confidence: 99%